Palmitoylethanolamide counteracts high-fat diet-induced gut dysfunction by reprogramming microbiota composition and affecting tryptophan metabolism - Pirozzi, Claudio; Coretti, Lorena; Opallo, Nicola; Bove, Maria; Annunziata, Chiara; Comella, Federica; Turco, Luigia; Lama, Adriano; Trabace, Luigia; Meli, Rosaria; Lembo, Francesca; Mattace Raso, Giuseppina (Frontiers in Nutrition, 2023)
Obesity is associated with gastrointestinal (GI) tract and central nervous system (CNS) disorders. High-fat diet (HFD) feeding-induced obesity in mice induces dysbiosis, causing a shift towards bacteria-derived metabolites with detrimental effects on metabolism and inflammation: events often contributing to the onset and progression of both GI and CNS disorders. Palmitoylethanolamide (PEA) is an endogenous lipid mediator with beneficial effects in mouse models of GI and CNS disorders. However, the mechanisms underlining its enteroprotective and neuroprotective effects still need to be fully understood. Here, we aimed to study the effects of PEA on intestinal inflammation and microbiota alterations resulting from lipid overnutrition. Ultramicronized PEA (30 mg/kg/die per os) was administered to HFD-fed mice for seven weeks starting at the 12th week of HFD regimen. At the termination of the study, the effects of PEA on inflammatory factors and cells, gut microbial features and tryptophan-kynurenine metabolism were evaluated. PEA regulates the crosstalk between the host immune system and gut microbiota via rebalancing colonic TRP metabolites. PEA treatment reduced intestinal immune cell recruitment, inflammatory response triggered by HFD feeding, and corticotropin-releasing hormone levels. In particular, PEA modulated HFD-altered tryptophan (TRP) metabolism in the colon, rebalancing serotonin (5-HT) turnover and reducing kynurenine levels. These effects were associated with a reshaping of gut microbiota composition through increased butyrate-promoting/producing bacteria, such as Bifidobacterium, Oscillospiraceae and Turicibacter sanguinis, with the latter also described as 5-HT sensor. These data indicate that the restructuring of gut microbiota following PEA supplementation promotes host 5-HT biosynthesis, which is crucial in regulating intestinal function.